Interaction of two complementary fragments of the bovine spinal cord myelin basic protein with phosphatidylglycerol bilayers, studied by 2H and 31P NMR spectroscopy. - Hayer-Hartl, M; Brophy, P; Marsh, D; Watts, A (1993)
The interaction of two complementary fragments of myelin basic protein from bovine spinal cord with bilayers of dimyristoylphosphatidylglycerol has been studied by broad line 2H and 31P NMR. The fragments, produced by cleavage at the single tryptophan, consist of an N-terminal portion of molecular mass 12.6 kDa and a C-terminal portion of molecular mass 5.8 kDa. The phosphatidylglycerol lipid was deuterated at all three segments of the glycerol headgroup. The approximately linear dependence of the 2H quadrupole splittings and 31P chemical shift anisotropy on protein/lipid ratio in the complexes indicates that the lipids interacting with the protein fragments were in fast exchange on the NMR time scale (approximately 10(-4)-10(-5) s). The relative gradients of the dependence on protein/lipid ratio of both these parameters decrease with the size of the protein fragment and correlate reasonably well with both the net charge on the protein and the lipid binding stoichiometries in the absence of salt. The results are therefore consistent with a model in which the perturbation of the quadrupole splittings either is determined by the net surface potential or is constant for the different protein fragments. Either possibility is consistent with the reduced activity of the fragments relative to the whole protein.